Polyreactive natural antibodies in transplantation. Issue 1 (February 2017) - Zorn, Emmanuel; See, Sarah B.
Abstract : Purpose of review: Antibody-mediated rejection (ABMR), especially in its chronic manifestation, is increasingly recognized as a leading cause of late graft loss following solid organ transplantation. In recent years, autoantibodies have emerged as a significant component of the humoral response to allografts alongside anti-human leukocyte antigen antibodies. These include polyreactive antibodies also known as natural antibodies (Nabs) secreted by innate B cells. A hallmark of Nabs is their capacity to bind altered self such as oxidized lipids on apoptotic cells. This review provides an overview of these overlooked antibodies and their implication in the pathophysiology of ABMR. Recent findings: New evidence reported in the past few years support a contribution of immunoglobulin (Ig) G Nabs to ABMR. Serum IgG Nabs levels are significantly higher in patients with ABMR compared with control kidney transplant recipients with stable graft function. Pretransplant IgG Nabs are also associated with ABMR and late graft loss. IgG Nabs are almost exclusively of the IgG1 and IgG3 subclasses and have the capacity to activate complement. Summary: In conclusion, Nabs are important elements in host immune responses to solid organ grafts. The recent description of their implication in ABMR and late kidney graft loss warrants further investigation into their pathogenic potential.